2010
DOI: 10.1111/j.1365-2761.2010.01181.x
|View full text |Cite
|
Sign up to set email alerts
|

Indian isolates of white spot syndrome virus exhibit variations in their pathogenicity and genomic tandem repeats

Abstract: To detect genomic variation of white spot syndrome virus (WSSV) isolates from different geographical regions of India, the variable number of the tandem repeat (VNTR) region of the ORF 94 (Thailand WSSV isolate - GeneBank Accession No. AF369029) was analysed using five specific sets of primers. Analysis of 70 WSSV-positive samples showed the presence of 14 different genotypes of WSSV with VNTRs ranging from 2 to 16 tandem repeats with the majority (85.47%) having 6-12 tandem repeats. Occurrence of different ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…The present report is based on three minisatellites ORF 75, 94 and 125. Application of these methods for typing WSSV isolates has been reported widely from the shrimp growing countries in the world (Dieu et al, 2004;Hoa et al, 2012;Gonzalez-Galaviz et al, 2013) while similar studies are limited from India (Musthaq et al, 2006;Pradeep et al, 2008;John et al, 2010) and the present study is the first report of WSSV genotyping from the state of Gujarat.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…The present report is based on three minisatellites ORF 75, 94 and 125. Application of these methods for typing WSSV isolates has been reported widely from the shrimp growing countries in the world (Dieu et al, 2004;Hoa et al, 2012;Gonzalez-Galaviz et al, 2013) while similar studies are limited from India (Musthaq et al, 2006;Pradeep et al, 2008;John et al, 2010) and the present study is the first report of WSSV genotyping from the state of Gujarat.…”
mentioning
confidence: 69%
“…Information on the status of the disease in the shrimp farming regions is vital for developing suitable prevention and control strategies. Report on the incidence of WSSV and further characterisation has mostly been restricted to some of the southern Indian states like Andhra Pradesh, Tamil Nadu, Kerala and Karnataka (Otta et al, 1999;Vaseeharan et al, 2003;Pradeep et al, 2008;John et al, 2010) where large scale shrimp culture were practiced. However, such kind of information is not available from Gujarat where, major shrimp growing developed lately.…”
mentioning
confidence: 99%
“…1B−E, Table 1). ORF94 and ORF125 VNTR types have been used widely to distinguish WSSV strains (Wongteerasupaya et al 2003, Hoa et al 2005, 2011, and many WSSV strains have been associated with disease at shrimp farms in India (Syed Musthaq et al 2006, Pradeep et al 2008, John et al 2010, Walker et al 2011a. The VNTR variations detected were thus not unexpected considering the different species examined and the fact that the diseased shrimp had been sourced from different farms in different regions of South India.…”
Section: Genotyping Of Wssv Strainsmentioning
confidence: 99%
“…These variables loci have been considered as important molecular markers for WSSV genotyping. The single nucleotide mutations, including deletions, insertions, and single nucleotide polymorphisms (SNP) have been suggested as markers for genetic diversity studies of WSSV (John et al, 2010;Hoa et al, 2011;González-Galaviz et al, 2013).…”
mentioning
confidence: 99%
“…This region shows more variation, with a wide range of compound repeat units (RUs) between the WSSV isolates originating from farming and wild hosts (Wongteerasupaya et al, 2003;Dieu et al, 2004;Musthaq et al, 2006;Pradeep et al, 2008;John et al, 2010;González-Galaviz et al, 2013). Several studies have suggested a correlation between the RUs of ORF94 and WSSV virulence as follows: the fewer RUs (<9) the higher mortality rate in shrimps (Waikhom et al, 2006;Pradeep et al, 2008;Hoa et al, 2012).…”
mentioning
confidence: 99%